NLRP3 inflammasome activation contributes to the pathogenesis of rheumatoid arthritis. (16th September 2018) - Guo, C; Fu, R; Wang, S; Huang, Y; Li, X; Zhou, M; Zhao, J; Yang, N
Summary: Nucleotide-binding, oligomerization domain (NOD)-like receptor family, pyrin domain containing 3 (NLRP3) gene polymorphism was reported to be associated with susceptibility, disease activity or anti-tumour necrosis factor (TNF) treatment response in rheumatoid arthritis (RA). However, the roles of NLRP3 inflammasome in the development of RA have not yet been elucidated fully. The present study aimed to study the role of NLRP3 inflammasome in RA. NLRP3 inflammasome activation in synovial tissues from RA and osteoarthritis (OA) patients were assessed by Western blot. Active caspase-1 in synovia was stained by a FAM-FLICA caspase-1 probe. Mice with collagen-induced arthritis (CIA) were treated with MCC950, a selective NLRP3 inhibitor, or vehicle for 2 weeks. The clinical score of arthritis, synovial inflammation and cartilage erosion were assessed. Proinflammatory cytokines were measured by enzyme-linked immunosorbent assay (ELISA). The results showed that NLRP3 inflammasome was highly activated in both synovia from RA patients and CIA mice. Activation of NLRP3 inflammasome occurred mainly in the infiltrating monocyte/macrophages in synovia, but not in fibroblast-like synoviocytes. Treatment with MCC950 resulted in significantly less severe joints inflammation and bone destruction. NLRP3 inflammasome activation in the synovia was inhibited significantly by MCC950 with reduced production of interleukin (IL)-1β. The inhibition of NLRP3 inflammasome activation by MCC950 was confirmed further in a human monocytic cell line, THP-1. In conclusion, NLRP3 inflammasome is involved in the pathogenesis of RA. Targeting NLRP3 inflammasome with a small molecule inhibitor might be a novel therapeutic strategy for RA. Graphical Abstract: